Factors associated with high consumption of soft drinks among Australian secondary-school students - Scully, M.; Morley, B.; Niven, P.; Crawford, D.; Pratt, Steve; Wakefield, M. (Cambridge University Press, 2017)
Copyright © The Authors 2017Objective: To examine demographic and behavioural correlates of high consumption of soft drinks (non-alcoholic sugar-sweetened carbonated drinks excluding energy drinks) among Australian adolescents and to explore the associations between high consumption and soft drink perceptions and accessibility. Design: Cross-sectional self-completion survey and height and weight measurements. Setting: Australian secondary schools. Subjects: Students aged 12–17 years participating in the 2012–13 National Secondary Students’ Diet and Activity (NaSSDA) survey (n 7835). Results: Overall, 14 % of students reported consuming four or more cups (=1 litres) of soft drinks each week (‘high soft drink consumers’). Demographic factors associated with high soft drink consumption were being male and having at least $AU 40 in weekly spending money. Behavioural factors associated with high soft drink consumption were low fruit intake, consuming energy drinks on a weekly basis, eating fast foods at least once weekly, eating snack foods =14 times/week, watching television for >2 h/d and sleeping for <8 h/school night. Students who perceived soft drinks to be usually available in their home, convenient to buy and good value for money were more likely to be high soft drink consumers, as were students who reported usually buying these drinks when making a beverage purchase from the school canteen/vending machine. Conclusions: High soft drink consumption clusters with other unhealthy lifestyle behaviours among Australian secondary-school students. Interventions focused on reducing the availability of soft drinks (e.g. increased taxes, restricting their sale in schools) as well as improved education on their harms are needed to lower adolescents’ soft drink intake.